PENGARUH PENAMBAHAN LIMBAH CAIRAN JAGUNG TERHADAP KUALITAS DAN KUANTITAS BIOGAS DARI KOTORAN SAPI - I Wayan Joniarta; Febrian Purnama; I Made Mara; I Kade Wiratama (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2026)
Biogas is one of the alternative energies that can be utilized to meet fuel energy needs. It originates from the fermentation process of biomass, such as cow dung. This research focuses on producing biogas from cow dung with the addition of corn waste water to determine the influence of adding corn waste water on the quality and quantity of the generated biogas. Treatments were applied by varying the composition of cow dung with corn waste water (A, B, C) and cow dung with water (D) as a control. The successive compositions created were composition A (1:1j), composition B (1:2j), composition C (1:3j), and composition D (1:1a), each repeated three times, and the study was conducted for 30 days. The research results indicate that with the addition of corn waste water, the highest quantity of biogas was obtained in composition A, amounting to 1168.08 cm3, while the lowest quantity was obtained in composition B, totaling 791.21 cm3. Regarding the quality testing of biogas with the addition of corn waste water, the highest quality was observed in composition A at 49.76%, whereas the lowest quality was found in composition B at 23%. However, in composition D, which consists of cow dung biogas with water demonstrated superior quality and quantity, with a quality value of 52.82% and a quantity of 1384.05 cm3. The data obtained suggest that corn waste water may not be as effective as a supplementary material for the mixture of cow dung biogas.